Chiasm, Flesh and Nature. Merleau-Ponty and the Problem of Mediality - Fagioli, Nicolás (2021)
“Chiasm, Flesh and Nature. Merleau-Ponty and the Problem of Mediality”. The notion of flesh, belonging to the last stage of Merleau-Ponty’s thought, occupies a decisive place in specialized research on the author. However, few publications highlight the immense influence of the latter in current thought, especially in the post-humanist and materialist currents of contemporary philosophy. We propose, in the pages that follow, to analyze this category from the point of view of a philosophy of relationship, interpreting it from the figure of mediality or relating them to a notion of medium. For this, in the first part, we will elucidate the notion of medium used in Phenomenology of Perception and the postulation of experience as a starting point. In the second part, we will specify the multiple dimensions in which the notion of flesh unfolds in the late philosophy of the author. Once the epistemological, phenomenological and ontological aspects of the ontology of the flesh have been addressed, its philosophical potential will be analyzed, projecting the treatments for the problems of nature, an issue that we consider of vital importance for current philosophical reflections.